2014
DOI: 10.1371/journal.pone.0111920
|View full text |Cite
|
Sign up to set email alerts
|

Dacarbazine Combined Targeted Therapy versus Dacarbazine Alone in Patients with Malignant Melanoma: A Meta-Analysis

Abstract: BackgroundMalignant melanoma is the most aggressive and deadly form of skin cancer. Dacarbazine (DTIC) has been the approved first-line treatment for metastatic melanoma in routine clinical practice. However, response rates with single-agent DTIC are low. The objective of this study was to compare the efficacy and safety of DTIC with or without placebo and DTIC-based combination therapies in patients with advanced metastatic melanoma.MethodsWe searched from electronic databases such as The Cochrane Library, ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…Active chemotherapies in MM include alkylating agents such as dacarbazine (DTIC), temozolomide (TMZ) and fotemustine (FM). DTIC gives an overall response rate of only 10–15% with a complete response in less than 5% of patients and a survival of 7–8 months [ 9 ]. Similar overall response rates were achieved with both TMZ and FM.…”
Section: Introductionmentioning
confidence: 99%
“…Active chemotherapies in MM include alkylating agents such as dacarbazine (DTIC), temozolomide (TMZ) and fotemustine (FM). DTIC gives an overall response rate of only 10–15% with a complete response in less than 5% of patients and a survival of 7–8 months [ 9 ]. Similar overall response rates were achieved with both TMZ and FM.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several drugs have been approved by the Food and Drug Administration for malignant metastatic melanoma, e.g. dacarbazine (DNA alkylating agent) [5], interleukin-2 [6], ipilimumab(CTLA-4 blockade) [7], vemurafenib and dabrafenib (anti-BRAF) [8]. Compared with chemotherapy, the potent specific BRAF inhibitors vemurafenib and dabrafenib have significantly improved response rates, along with progression-free and overall survival, in patients with metastatic melanoma with BR AFV600E mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the involvement of TRPA1 in chemotherapy‐induced pain, a recent study showed its involvement in melanoma‐induced cancer pain . Because dacarbazine is the main chemotherapeutic agent used to treat metastatic melanoma, we performed a cancer pain protocol by associating the B16‐F10 melanoma tumor cell inoculation with dacarbazine administration. The association of tumor cells and dacarbazine did not produce additional nociceptive behavior because maximum nociception was achieved after a single dacarbazine administration.…”
Section: Discussionmentioning
confidence: 99%